Metal(ii)–organic frameworks with 3, 3′-diphenyldicarboxylate and 1, 3-bis(4-pyridyl)propane: preparation, crystal structures and luminescence. Issue 48 (20th November 2015) - Fan, Ting-Ting; Li, Jia-Jia; Qu, Xiang-Long; Han, Hong-Liang; Li, Xia
Abstract : 3D frameworks were constructed from Zn(ii )/Cd(ii )/Cu(ii ), 3, 3′-diphenyldicarboxylate, and 1, 3-bis(4-pyridyl)propane. The Zn-framework was used as a fluorescent probe to sense benzaldehyde. Abstract : Mixing transition metal(ii ) salts with 3, 3′-diphenyldicarboxylic acid (3, 3′-H2 dpdc) and 1, 3-bis(4-pyridyl)propane (bpp) led to the complexes [M(3, 3′-dpdc)bpp] (M = Zn1, Cd2 ) and [Cu2 (3, 3′-dpdc)2 (bpp)] (3 ). These complexes were characterized by single-crystal X-ray diffraction.1 possesses a four-fold interpenetrating 3D diamondoid framework consisting of Zn-3, 3′-dpdc and Zn-3, 3′-dpdc-bpp helices and has a 6 6 topology net with 4-c tetrahedral Zn(ii ) nodes.2 exhibits a 3D framework consisting of Cd-3, 3′-dpdc-bpp two/four-stranded helices and has a 6-c 3 6 ·4 12 ·5 4 ·6 6 topology with binuclear blocks.3 has a three-fold interpenetrating 3D framework with a 6-c 3 12 ·4 28 ·5 5 topology based on binuclear blocks. Cu-3, 3′-dpdc and Cu-bpp-3, 3′-dpdc helices are formed. The metal centers play a crucial role in the system structure direction. The luminescence properties of these compounds were investigated. The results show that1 can be used as a fluorescent probe to detect benzaldehyde and sensitize Tb(iii ) luminescence. Notably, addition of Tb(iii ) into the Zn-MOF (1 ) greatly enhanced its ability to detect benzaldehyde.